COMPARATIVE LEGAL ANALYSIS ON THE COMPETENCE OF THE INDONESIA’S FINANCIAL SERVICES AUTHORITY AND MONETARY AUTHORITY OF SINGAPORE ON THE ENFORCEMENT OF INSIDER TRADING LAWS - Fabian Jonathan; Fajar Sugianto; Tomy Michael (Bank Indonesia, 2023)
This article investigates the competencies of both Indonesian and Singaporean capital market supervisory and regulatory bodies, namely Otoritas Jasa Keuangan and the Monetary Authority of Singapore. It further assesses the effectiveness of each body in enforcing laws prohibiting insider trading specifically. It shall further evaluate the passiveness portrayed by the Indonesian counterpart when it comes to the eradication of day trading activities in the market as well as variables that are weighed in its implementation. A normative-empirical method is used for this article as it considers legal principles and legal systems, following a comparative approach. The materials relied on for this article include an interview with a capital market lawyer, an analysis of the law and other supporting documents, and a comparative study. The nature of competence for Indonesia and Singapore’s capital market supervisory and regulatory bodies is quite similar which adopt integrated approaches towards regulation and supervision of the capital market and with adequate authority to enforce their mandates. Since 2012, OJK has replaces the role of Bapepam-LK to administer the Capital Market Law as an independent body. OJK is responsible for enacting rules and other oversight of the sector.